LEARNING HADITH: Preventive Efforts Against Hadith Maudhu in Islamic Educational Institutions (Pesantren) in Indonesia - Purwidianto, Purwidianto (Al-Bukhari : Jurnal Ilmu Hadis, 2024)
This article is based on the emergence of hadiths maudhu circulating in the society. In reality, the general public obtains religious knowledge from the graduates of Pesantren (Islamic boarding schools). Thus, indirectly, the Pesantren contribute to the spread of hadiths maudhu in the society. This research was conducted by examining Pesantren in general by referring to literature related to education in Islamic boarding schools. The research method used is a descriptive-analytical method of the existing phenomena. From this research, it is concluded that Pesantren play a role in the circulation of hadiths maudhu in the society. This role was seen in the Pesantren's educational system, particularly in relation to hadith studies, which did not refer to the primary hadith books but used books containing specific hadiths without explaining their authenticity. The hadiths they studied were then conveyed to the society, which became the initial source of hadiths maudhu.